Problematic internet use and shyness among Chinese adolescents: a moderated mediation model - Sun, Hong; Yu, Yang (Frontiers in Psychology, 2024)
The potential adverse effects of problematic internet use (PIU) on individuals' offline personalities have been a significant concern in internet psychology. This study aimed to investigate the negative effects of PIU on shyness and the mediating role of self-regulation, as well as the moderating role of social comparison orientation. A total of 1322 adolescents from China participated in the survey. The results indicated that: (1) PIU positively predicted shyness;(2) self-regulation partially mediated the relationship between PIU and shyness; (3) social comparison orientation moderated the mediation effect, specifically buffering the negative prediction of PIU on self-regulation, but exacerbating the negative predictive effect of self-regulation on shyness. The findings explored and verified the psychosocial effects of the internet, contributing to a deeper understanding of how PIU affects individual personality traits and offering insights into its role in broader social behavior patterns.